Graphene-gold metasurface architectures for ultrasensitive plasmonic biosensing - Zeng, Shuwen (2015)
Graphene–gold metasurface architectures that can provide significant gains in plasmonic detection sensitivity for trace-amount target analytes are reported. Benefiting from extreme phase singularities of reflected light induced by strong plasmon-mediated energy confinements, the metasurface demonstrates a much-improved sensitivity to molecular bindings nearby and achieves an ultralow detection limit of 1 × 10−18 M for 7.3 kDa 24-mer single-stranded DNA.